2010
DOI: 10.9755/ejfa.v22i5.4823
|View full text |Cite
|
Sign up to set email alerts
|

Production of transgenic Indica rice (Oryza sativa L.) Cv. MR 81 via particle bombardment system

Abstract: Embryogenic callus of rice (Oryza sativa L. cv. MR 81 and Taipei 309) were bombarded with the recombinant pRQ6 construct carrying the hygromycin phosphotransferase (hph) and β-glucuronidase (gusA) genes using particle bombardment system. Transformed embryogenic callus that are capable of growing on selection media containing 50mg/L hygromycin B developed GUS expression based on blue colouration in the presence of 5-bromo-4-chloro-3-glucuronic acid. These embryogenic callus consisted of both transformed (blue) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In this study, suspension EC, were chosen as the starting material for oil palm transformation as they are easily regenerated into plantlets (Tarmizi et al, 2008). Embryogenic cultures were also reported to be a good target tissue as they provided a source of dividing cells that were recognized as the most competent cells for genetic transformation of pine species, cassava, sweet potato, rice, and garlic (Trontin et al, 2007; Bull et al, 2009; Zang et al, 2009; Rahman et al, 2010; Alvarez and Ordás, 2013; Lagunes-Fortiz et al, 2013). The use of highly regenerative tissue as target for transformation often results in the regeneration of a large number of independently transformed lines.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, suspension EC, were chosen as the starting material for oil palm transformation as they are easily regenerated into plantlets (Tarmizi et al, 2008). Embryogenic cultures were also reported to be a good target tissue as they provided a source of dividing cells that were recognized as the most competent cells for genetic transformation of pine species, cassava, sweet potato, rice, and garlic (Trontin et al, 2007; Bull et al, 2009; Zang et al, 2009; Rahman et al, 2010; Alvarez and Ordás, 2013; Lagunes-Fortiz et al, 2013). The use of highly regenerative tissue as target for transformation often results in the regeneration of a large number of independently transformed lines.…”
Section: Resultsmentioning
confidence: 99%
“…A high level of nitrogen plays a vital role in cell division and elongation. (Hasanuzzaman et al, 2010) reported an increase in tiller number per unit under the combined application of organic and inorganic fertilizer treatment. Organic fertilizer sources offer more balanced nutrition, especially micronutrients which positively affect the number of tillers in rice plants (Belefant-Miller, 2007).…”
Section: Numbers Of Tillersmentioning
confidence: 99%
“…A maximum number of effective tillers per meter square were observed on T2 (75%NPK + 25% FYM) which was 315.750 per meter square and was statistically at par with T1, T3, and T4 while, a minimum number of effective tillers per meter square was observed on T5, which was 266.250 per square meter which is highly significant with T2. (Hasanuzzaman et al, 2010) reported an increase in tiller number per unit area under the combined application of organic and inorganic fertilizer treatment. This could have been due to the availability of a high level of nitrogen which plays a vital role in cell division and elongation.…”
Section: Yield Attributing Parameters Net Effective Tillersmentioning
confidence: 99%
“…Based on the present study, similar results have been observed under organic fertilizer applications. Hasanuzzaman et al (2010) obtained the plant height ranging from 74.6 cm to 106.5 cm for rice plants in wetland field conditions. Plant height is a crucial characteristic that affects the plant status and capacity for yield (Yan et al, 1998).…”
Section: Plant Height Of Rice Varieties At Flowering Stagementioning
confidence: 99%